Monitors or certifiers? Different roles of private equity firms at different timing of investments - Hsu WH; Young M (Massey University)
This paper examines the market response to the announcements of receiving investments from the private equity (PE) firms. It is found that the positive market reaction is due to the certification effect that the PE firms may have inside information about the company value. This insider hypothesis is also found in the subsample of repeated investments: market reacts positively when the underperformed companies receive funding from the same PE firms again. On the other hand, when the companies receive investments from the PE firms for the first time, the investors recognises the monitoring role of the PE investors as well as their certification role.